Evaluating Cholinergic Receptor Expression in Guinea Pig Primary Auditory and Rostral Belt Cortices After Noise Damage Using [H]Scopolamine and [F]Flubatine Autoradiography - Taylor J. Forrest MS; Timothy J. Desmond MS; Mohamad Issa MD; Peter J. H. Scott PhD; Gregory J. Basura MD, PhD (Molecular Imaging)
Noise-induced hearing loss leads to anatomic and physiologic changes in primary auditory cortex (A1) and the adjacent dorsal rostral belt (RB). Since acetylcholine is known to modulate plasticity in other cortical areas, changes in A1 and RB following noise damage may be due to changes in cholinergic receptor expression. We used [ 3 H]scopolamine and [ 18 F]flubatine binding to measure muscarinic acetylcholine receptor (mAChR) and nicotinic acetylcholine receptor (nAChR) expression, respectively, in guinea pig A1 and RB 3 weeks following unilateral, left ear noise exposure, and a temporary threshold shift in hearing. [ 3 H]Scopolamine binding decreased in right A1 and RB (contralateral to noise) compared to sham controls across all cortical layers. [ 18 F]Flubatine binding showed a nonsignificant upward trend in right A1 following noise but only significantly increased in right RB and 2 layers of left RB (ipsilateral to noise). This selective response may ultimately influence cortical plasticity and function. The mechanism(s) by which cholinergic receptors are altered following noise exposure remain unknown. However, these data demonstrate noise exposure may differentially influence mAChRs that typically populate interneurons in A1 and RB more than nAChRs that are traditionally located on thalamocortical projections and provide motivation for cholinergic imaging in clinical patient populations of temporary or permanent hearing loss.